Effects of Conservative Oxygen Therapy versus Conventional Oxygen Therapy on the Mortality in ICU Patients: A Meta-Analysis - Xinyu Jiang; Dong Qiu (Canadian Respiratory Journal)
Objective. To compare the effects of conservative oxygen therapy and conventional oxygen therapy on the mortality of critically ill patients in ICU. Methods. Searching for randomized controlled clinical trials (RCT) on the effect of conservative oxygen therapy and conventional oxygen therapy on the mortality of critically ill patients in computer databases, including PubMed, Embase, Cochrane Library, CNKI, VIP, and Wanfang, with postdate before August 2022. We have two researchers evaluating the quality of the literature included and extracting data as per the inclusion and exclusion criteria and then analyzed it with RevMan 5.4 statistical software. Primary outcome included short-term mortality (28-day mortality or ICU mortality); secondary outcome included 90-day mortality, ICU length of stay, hospital length of stay, incidence of new organ dysfunction in ICU, incidence of new infection in ICU, and incidence of ICUAW. Results. A total of 5779 subjects were included in 10 articles, including 2886 in the conservative oxygen therapy group and 2893 in the conventional oxygen therapy group. The meta-analysis showed that conservative oxygen therapy had an advantage over conventional oxygen therapy in terms of short-term mortality (P=0.03). Subgroup analysis based on different conservative oxygen targets showed that this advantage was statistically significant when the target is set above 90% (RR = 0.76, 95% CI = 0.62∼0.94, P=0.01), while there was no significant difference between conservative oxygen therapy and conventional oxygen therapy when the target is set below 90% (RR = 0.95, 95% CI = 0.79∼1.16, P=0.63). In addition, in terms of the incidence of new infections in the ICU (P=0.03) and the incidence of ICUAW (P=0.03), conservative oxygen therapy also had advantages over conventional oxygen therapy, and the difference was statistically significant. But in terms of 90-day mortality (P=0.61), ICU length of stay (P=0.96), hospital length of stay (P=0.47), and incidence of new organ dysfunction in ICU (P=0.61), there was no significant difference between conservative oxygen therapy and conventional oxygen therapy. Conclusion. Compared with conventional oxygen therapy, conservative oxygen therapy can reduce the short-term mortality of severe patients, especially when the conservative oxygen therapy target is set above 90%. And it can also reduce the incidence of ICU new infections and ICUAW, while having no effect on 90-day mortality, ICU length of stay, and hospital length of stay.